Call the midwife. Season fourteen [videorecording (DVD)] - Thomas, Heidi, 1962- (BBC, 2025)
The midwives enter the 1970s, which brings with it new challenges for Nonnatus House - and to British society. The Seventies start as they mean to go on, with Nonnatus House plunged into disarray when activists staging a bid for independence blockade access to the Isle of Dogs. Amid the poverty and uncertainty of life in a declining Docklands, the midwives must also face cases of manic depression, gonorrhea, spina bifida, abortion and an apparently immaculate conception.